2021
DOI: 10.18087/cardio.2020.12.n1342
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 management in heart transplanted recipients: registry of Almazov National Medical Research Centre

Abstract: Aim      This study presents the experience of managing patients with COVID-19 after cardiac transplantation (CT).Material and methods  Infectious complications (IC) following CT are a leading cause for morbidity and mortality. A prolonged incubation period, atypical IC symptoms, and originally altered results of laboratory and instrumental diagnosis are characteristic of recipients due to immunosuppression. In 2020, the coronavirus infection (COVID-19) rapidly spread worldwide, and timely diagnosis and search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…Состояние после трансплантации органа с поддерживающей иммуносупрессивной терапией служит благоприятным фоном для манифестации инфекционной болезни. При этом факт иммуносупрессии не только повышает вероятность развития инфекционных осложнений, но и может влиять на клиническое течение болезни [6]. У пациентов, перенесших трансплантацию и получающих супрессивную терапию, в случае развития инфекционной болезни возможно пролонгирование инкубационного периода, развитие стертых и абортивных форм инфекционного процесса [7].…”
Section: Discussionunclassified
“…Состояние после трансплантации органа с поддерживающей иммуносупрессивной терапией служит благоприятным фоном для манифестации инфекционной болезни. При этом факт иммуносупрессии не только повышает вероятность развития инфекционных осложнений, но и может влиять на клиническое течение болезни [6]. У пациентов, перенесших трансплантацию и получающих супрессивную терапию, в случае развития инфекционной болезни возможно пролонгирование инкубационного периода, развитие стертых и абортивных форм инфекционного процесса [7].…”
Section: Discussionunclassified
“…We also showed that remote counseling of patients with a transplanted heart, compliance with the continuity of treatment at the place of residence, and account for the recommendations of supervising transplant doctors contributed to the timely diagnosis of infection, the rapid initiation of therapy, and the course of COVID-19 without complications. Reducing the use of immunosuppressive drugs (antiproliferative) for up to 14 days contributed to the fight against infection and was not accompanied by an acute crisis of rejection and/or a decrease in the function of the graft [ 20 ].…”
mentioning
confidence: 99%